(untitled) (Journal of Social Sciences Review, 2023)
This research article interprets Gordimer’s novels as an expression of resistance against black oppression in pre-apartheid South Africa. Looking at her insightful and evocative depictions of some of the major political issues in selected works, the present work discusses their relevance and importance in the contemporary world. The current paper uses a qualitative approach to examine the impact of the apartheid regime on individuals and communities in South Africa, as well as the impact of political events on individuals, the author’s preoccupation with power and its impact on people’s lives as well as her treatment of race and related issues. Gordimer highlights how political events and power structures can influence and disrupt the lives of individuals and communities through her characters and their experiences. Her works offer a vivid and insightful critique of how apartheid regimes and other political systems are used to control and manipulate individuals and communities.